P1-S6.51 Antiretroviral therapy, sexual behaviour, and their simulated impact on HIV epidemiologic trends in Uganda. (10th July 2011) - Shafer, L A; Nsubuga, R; Chapman, R; O'Brien, K; Mayanja, B; White, R
Abstract : Background: Debate exists concerning the potential impact of ART on the HIV epidemic in Africa. We combine empirical evidence for sexual behaviour change in response to ART in a Ugandan cohort, with mathematical modelling, to examine the likely impact of ART on the HIV epidemic, accounting for potential behaviour change. Methods: Cohort participants are surveyed every 3 months on sexual behaviours. ART rollout began in 2004. Using regression, we examined potential associations between timing of ART initiation and sexual behaviour among HIV-infected, and timing of ART availability and sexual behaviour among HIV-uninfected. We then used a compartmental mathematical model to assess the impact of ART on HIV epidemiologic trends, under varying assumptions about rates of initiating ART and behaviour change. The model has been described previously in peer-reviewed literature. Results: We found no evidence of increased risk behaviour after ART initiation to levels higher than 2 years before initiation. There is some evidence of rising risk behaviour among HIV-uninfected people in response to ART availability. Among HIV-uninfected, the mean number of casual partners in the past 3 months fell from 0.02 in 2002 to 0.01 by 2004 and then rose to 0.03 by late 2008 (p for change in trend from declining to rising numbers of casual partners over the period 2002–2008=0.030). The mean number of new partners in the past 3 months fell from 0.13 in early 2002 to 0.02 in the late 2004. By 4th quarter of 2008, the number of new partners in the past 3 months had risen to 0.20 (p=0.058). Regardless of changing sexual behaviour, the model suggests that ART will reduce HIV incidence, but increase prevalence. This occurs even when ART initiation begins in HIV stage 2 (∼3 months after infection) and 90% of HIV-infected are on ART and the probability of transmission while on ART declines greatly (right panel of Abstract P1-S6.51 Figure 1 baseline of no ART displayed in left panel). The conditions required for ART to reduce prevalence had to be more extreme than this (left panel). Conclusions: Due to HIV+ people enjoying a longer life expectancy, and an insufficient drop in incidence, HIV prevalence will rise as a result of ART. Modelling suggests that even small increases in risky sexual behaviour will lead to further substantial increases in HIV prevalence. Policy makers are urged to continue promoting sex education, and be prepared for a higher than previously suggested number of HIV+ people in need of treatment.